Overview of the current status of familial hypercholesterolaemia care in over 60 countries - The EAS Familial Hypercholesterolaemia Studies Collaboration (FHSC). (October 2018) - ,; Vallejo-Vaz, Antonio J.; De Marco, Martina; Stevens, Christophe A.T.; Akram, Asif; Freiberger, Tomas; Hovingh, G. Kees; Kastelein, John J.P.; Mata, Pedro; Raal, Frederick J.; Santos, Raul D.; Soran, Handrean; et al.
Abstract: Background and aims: Management of familial hypercholesterolaemia (FH) may vary across different settings due to factors related to population characteristics, practice, resources and/or policies. We conducted a survey among the worldwide network of EAS FHSC Lead Investigators to provide an overview of FH status in different countries. Methods: Lead Investigators from countries formally involved in the EAS FHSC by mid-May 2018 were invited to provide a brief report on FH status in their countries, including available information, programmes, initiatives, and management. Results: 63 countries provided reports. Data on FH prevalence are lacking in most countries. Where available, data tend to align with recent estimates, suggesting a higher frequency than that traditionally considered. Low rates of FH detection are reported across all regions. National registries and education programmes to improve FH awareness/knowledge are a recognised priority, but funding is often lacking. In most countries, diagnosis primarily relies on the Dutch Lipid Clinics Network criteria. Although available in many countries, genetic testing is not widely implemented (frequent cost issues). There are only a few national official government programmes for FH. Under-treatment is an issue. FH therapy is not universally reimbursed. PCSK9-inhibitors are available in ∼2/3 countries. Lipoprotein-apheresis is offered in ∼60% countries, although access is limited. Conclusions: FH is a recognised public health concern. Management varies widely across countries, with overall suboptimal identification and under-treatment. Efforts and initiatives to improve FH knowledge and management are underway, including development of national registries, but support, particularly from health authorities, and better funding are greatly needed. Highlights: The EAS FHSC is an international initiative involving a network of investigators interested in FH from around 70 countries. Information on FH prevalence is lacking in most countries; where available, data tend to align with contemporary estimates. FH diagnosis and management varies widely across countries, with overall suboptimal identification and under-treatment. In most countries diagnosis primarily relies on DLCN criteria, and less frequently on Simon Broom or MEDPED. Therapy for FH is not universally reimbursed, and criteria vary across countries. Access to PCSK9i and apheresis is limited.